Potential of Sisal (Agave sisalana) Residues for Improving Sisal Plant Growth and Soil Residue Stocks in Bahia’s Circular Agriculture - Risely Ferraz-Almeida; Adelson Rodrigues de Oliveira; Clecivânia de Jesus Pinheiro; Joane Lima Oliveira; Valmir Freitas de Almeida; Everton Martins Arruda (Agronomy, 2025)
Brazil is considered one of the world’s most important sisal fiber producers (derived from Agave sisalana), with areas concentrated in the Bahia state. There has been a movement in agriculture toward a circular economic system (take-produce-consume-recycle). Based on this idea, the focus of this study was: (i) to estimate the theoretical available amount of sisal residues based on fiber and area productions; (ii) to monitor the use of sisal residues for improving sisal plant growth; and (iii) to monitor the residue stocks on surface soil with the application of sisal residues. Areas of sisal were visited periodically, monitoring the application of sisal residue on the soil surface. The results showed that there is an expressive production of sisal residues, mainly of green liquid, sisal pulp, and sisal ball. The application of sisal pulp on the soil surface, close to sisal plants, is an optimal alternative to improve sisal leaf development. The application of sisal residues on soil increased 50% of residue stocks with sizes lower than 10 cm. Based on the results, we concluded that the sisal residues have a great potential for improving sisal plant growth and soil residue stocks. More studies are required to improve circular agriculture in the sisal sector.